Environmental temperatures shape thermal physiology as well as diversification and genome-wide substitution rates in lizards - Garcia-Porta, Joan; Irisarri, Iker; Kirchner, Martin; Rodríguez, Ariel; Kirchhof, Sebastian; Brown, Jason L.; MacLeod, Amy; Turner, Alexander P.; Ahmadzadeh, Faraham; Albaladejo, Gonzalo; Crnobrnja-Isailovic, Jelka; De la Riva, Ignacio; et al. (Springer Nature, 2019)
Climatic conditions changing over time and space shape the evolution of organisms at multiple levels, including temperate lizards in the family Lacertidae. Here we reconstruct a dated phylogenetic tree of 262 lacertid species based on a supermatrix relying on novel phylogenomic datasets and fossil calibrations. Diversification of lacertids was accompanied by an increasing disparity among occupied bioclimatic niches, especially in the last 10 Ma, during a period of progressive global cooling. Temperate species also underwent a genome-wide slowdown in molecular substitution rates compared to tropical and desert-adapted lacertids. Evaporative water loss and preferred temperature are correlated with bioclimatic parameters, indicating physiological adaptations to climate. Tropical, but also some populations of cool-adapted species experience maximum temperatures close to their preferred temperatures. We hypothesize these species-specific physiological preferences may constitute a handicap to prevail under rapid global warming, and contribute to explaining local lizard extinctions in cool and humid climates.